George Eliot and Islamic Culture - Dallel Chenni (Cahiers Victoriens et Edouardiens)
This essay is the first of a series which explores George Eliot's perception of Islam at a time when many Victorian thinkers vigorously debated the definition, origins and specificities of Islamic culture. Using as primary sources Eliot’s notebooks, letters, journals, book reviews and essays, the article demonstrates that Eliot’s original curiosity about Islam arose in conjunction with her keener, more sympathetic interest in Judaism, and examines whether Eliot’s reading of English and European intellectuals interested in Islamic culture had any impact on her own attitude towards Islam. Indeed, while Eliot’s various and dispersed comments often reflect a shallow, essentially prejudiced view of the matter, her writing in fact evolved towards more tolerant views over the years.